KUALITAS PELAYANAN KESEHATAN PASIEN BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) DI PUSKESMAS TALISE KOTA PALU - Dyo Moh Sabda; Siti Nurfadila; Al Munawwara; Meinar Meinar; Mustaina N; Intam kurnia; Dandan haryono (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Health Insurance is a health protection guarantee provided to (BPJS) participants. The Health Social Security Organizing Agency (BPJS) is a legal entity established to administer the Health Insurance program. Service commitment is the commitment of the first level health facility in improving the quality of service seen from the achievement of agreed individual health service indicators. The purpose of this study was to determine. Overview of BPJS Health services to patients at the Talise health center in the city of Palu. This study aims to describe the quality of service of the Talise puskemas to user patients (BPJS). This study uses qualitative research methods with data collection techniques by means of interviews and observations. Based on the results of the study, it can be seen that the quality of service (BPJS) at the Talise health center in the city of Palu still has shortcomings and is not optimal, including medical equipment and medicines.